URGENITAS KEPEMIMPINAN KEPALA SEKOLAH DALAM PENINGKATAN KOMPETENSI SOSIAL DI SEKOLAH MENENGAH - Zahara Mustika (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2022)
The leadership of the school principal in improving the social competency of teachers is something that is urgent in schools, because the principal as the top leader determines the progress and decline of a school organization. But also the social competence of teachers can be influenced by the principal's leadership style, strategies and policies in increasing these competencies. This study aims to reveal: 1) leadership styles, 2) policies and strategies, and 3) challenges and opportunities from school principals in strengthening teacher social competence. The approach uses a qualitative type of descriptive research with data collection techniques using observation, interviews and documentation techniques. The research subjects were the school principal, deputy head of administration, and two teachers at SMP IT Nurul Ishlah. Data analysis was carried out through data reduction, data presentation and drawing conclusions. The validity of the researcher's data uses credibility, transferability, dependability and confirmability. The results of the study obtained that: the principal's leadership style, has a democratic leadership style and a charismatic leadership style. Principal strategies and policies by communicating politely and harmoniously by applying the principle of brotherhood to the teacher council, students, parents and the surrounding community, conducting training and seminars for teachers in order to improve social competence and teacher insight. Motivating teachers to be passionate about innovating and developing quality as educators, creating programs to strengthen teacher relationships with fellow teachers, students, parents of students and the community environment. While the challenges and opportunities for approaching are due to the diversity of backgrounds, the age of the teachers at school, and the opportunities for strengthening them by being invited to work together to improve quality and involve all school members in social and integrity actions